Potential Attractiveness of Olive Beneficial Insects to Flowering Weeds - Belo, A.D.F. (2011)
Nowadays, there is a growing concern about keeping olive groves in a good sanitary health with a decreasing input of pesticides. Increasing beneficial insect fauna is a novel, non-intrusive way to achieve this objective. To increase beneficial insect fauna, non-prey food availability must be enhanced, and that purpose can be attained by manipulating olive groves inter-rows natural weed vegetation. Amongst weeds naturally occurring in South Portugal olive grove inter-rows, 20 were chosen provided that they are nectar producers. Flowering period time and duration were additional choice criteria, ensuring that insects can feed on, at least, one flowering species at any time. In order to establish which weeds are more suitable to this purpose, their nectar production and accessibility for two natural olive beneficial insects - the parasitoid Psyttalia concolor and the pest predator Anthocoris nemoralis - were evaluated. Evaluation of floral morphology included measurements of the length of corolla tube (the distance between corolla insertion and the beginning of corolla lobes), length of whole corolla, major and minor width of corolla tube and diameter of corolla limb; all measurements were repeated on 30 corollas per species. Nectar production, concentration and sugar composition are also evaluated on 30 flowers per species. To protect flowers from insects visit and, therefore, nectar depletion, they were covered with bridal veil 24 h before collection. Nectar was extracted and quantified with capillary micropipettes (Drummond Microcaps®), and the sugar concentration was determined with a hand held refractometer (Atago®). Nectar was lyophilized for posterior composition determination through gas chromatography. Descriptive statistics of flower traits were calculated for each of the analyzed species. Classical statistical tests will be applied to correlate morphometric analyses of floral characteristics and nectar volume, concentration and composition will be searched for. After this initial phase, weed species attractiveness for Psyttalia concolor and Anthocoris nemoralis will be further evaluated with using an olfactometer. Research was financially supported by Fundação para a Ciência e Tecnologia (FCT), with partial funding from the European Fund for Regional Development, through the project PTDC/AGRAAM/ 100979/2008.